Sijori-GT Economic Cooperation for Three Decades: Examining Malaysia’s and Singapore’s FDI Commitments to Riau Islands - La Ode Nazaruddin; Qisthina Aulia (Center for Southeast Asian Social Studies (CESASS), 2022)
The Singapore-Johor-Riau Growth Triangle (Sijori-GT) was initiated by the government of Singapore, Malaysia, and Indonesia in 1989. It took advantage of complementarities among the involved regions. The peripheral regions were expected to reap benefits and gain spillovers from the extended metropolitan region of Singapore. In the age 30 years of the growth triangle, many scholars found great progress and challenges of the subregional economic cooperation such as unbalanced development and the assumably weak commitment of the participating countries in the Riau Islands. This research has the aim to investigate the tenable commitments of Singapore's and Malaysia's Foreign Direct Investment (FDI) in the Riau Islands. Using statistical data from Indonesia's Ministry of Investment from 1990 to 2020, this study compared FDI in Riau Islands by origin, and Singapore's and Malaysia's FDI by sector and subsector. The data was analyzed using the independent sample t-test for two-variable comparison and analysis of variance (posthoc test) for multiple-variable comparison. Finally, this study found that: firstly, the investment of Singapore was larger than that of Malaysia in the Riau Islands; secondly, Singapore specialized in its investment in the manufacturing sector having a better comparative advantage while Malaysia specialized in its investment in the non-manufacturing sector with potential assumed capabilities in halal-related sectors. The lesson-learned from Singaporean and Malaysian case is that dependence will determine the long-run commitment in subregional cooperation.